PENGARUH PERTUMBUHAN LABA, INVESTMENT OPPORTUNITY SET DAN INTENSITAS MODAL TERHADAP KUALITAS LABA - Karmila, Mila; Nofryanti (Publika Citra Media, 2025)
This study aims to determine, prove and obtain empirical evidence of the Influence of Profit Growth, Investment Opportunity Set and Capital Intensity on Earnings Quality. This study uses a quantitative approach and the data used is secondary data. The population in this study is Consumer Non-Cyclicals Companies listed on the Indonesia Stock Exchange for the period 2018-2023. The method in determining the sample uses purposive sampling. A sample of 33 companies was obtained with a period of 6 years so that the total number obtained was 198 sample data. The method used is multiple linear regression with the help of Eviews version 13 data processing. Profit Growth, Investment Opportunity Set and Capital Intensity simultaneously have an influence on Earnings Quality. Profit growth partially affects Earnings Quality, Investment Opportunity Set does not partially affect Earnings Quality, Capital Intensity does not partially affect Earnings Quality.